Willis Van Devanter papers - Van Devanter, Willis, 1859-1941.
Correspondence, letterbooks, legal records and briefs, speeches, lectures, and scrapbooks. Topics include Van Devanter's Cheyenne, Wyo., law practice, Wyoming and Republican Party politics, the 1896 election, Indian affairs, western land policy, and his service (1910-1937) as associate justice of the U.S. Supreme Court. Correspondents include Elmer B. Adams, Charles Fremont Amidon, Louis Dembitz Brandeis, Pierce Butler, A.C. Campbell, Joseph M. Carey, Clarence D. Clark, John H. Clarke, William R. Day, Oliver Wendell Holmes, William C. Hook, Charles Evans Hughes, Frank B. Kellogg, John W. Lacey, Frank W. Mondell, John Finis Philips, John C. Pollock, William A. Richards, John A. Riner, William Velpeau Rooker, Edward Terry Sanford, Harlan Fiske Stone, William H. Taft, Luther M. Walter, Francis E. Warren, and Sylvester G. Williams.
Lawyer, jurist, and Supreme Court justice.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Elmer B. -- 1842-1916 -- Correspondence; Amidon, Charles Fremont, -- 1856-1937 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Butler, Pierce, -- 1866-1939 -- Correspondence; Campbell, A. C. -- Correspondence; Carey, Joseph M. -- 1845-1924 -- Correspondence; Clark, Clarence D. -- 1851-1930 -- Correspondence; Clarke, John H. -- 1857-1945 -- Correspondence; Day, William R. -- 1849-1923 -- Correspondence; Holmes, Oliver Wendell, -- 1841-1935 -- Correspondence; Hook, William C. -- 1857-1921 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Kellogg, Frank B. -- 1856-1937 -- Correspondence; Lacey, John W. -- 1848-1936 -- Correspondence; Mondell, Frank W. -- 1860-1939 -- Correspondence; Philips, John Finis, -- 1834-1919 -- Correspondence; Pollock, John C., -- 1857-1937 -- Correspondence; Richards, William A. -- 1849-1912 -- Correspondence; Riner, John A. -- 1850-1923 -- Correspondence; Rooker, William Velpeau, -- approximately 1860-1934 -- Correspondence; Sanford, Edward Terry, -- 1865-1930 -- Correspondence; Stone, Harlan Fiske, -- 1872-1946 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Walter, Luther M. -- 1877-1947 -- Correspondence; Warren, Francis E. -- 1844-1929 -- Correspondence; Williams, Sylvester G. -- Correspondence; Republican Party (U.S. : 1854- ); United States. -- Supreme Court; Constitutional law -- United States; Elections -- United States -- 1896.; Indians of North America -- Government relations; Law -- United States; Practice of law -- Wyoming -- Cheyenne; Public lands -- West (U.S.); Wyoming -- History; Wyoming -- Politics and government; Jurists; Lawyers